2021
DOI: 10.2174/1573403x16666200129114330
|View full text |Cite
|
Sign up to set email alerts
|

Takotsubo Syndrome: Clinical Manifestations, Etiology and Pathogenesis

Abstract: : The purpose of the review is the analysis of clinical and experimental data on the etiology and pathogenesis of takotsubo syndrome (TS). TS is characterized by contractile dysfunction, which usually affects the apical region of the heart, lack of coronary artery obstruction, moderate increase in myocardial necrosis markers, prolonged QTc interval (in 50% of patients), sometimes elevation of ST segment (in 19% of patients), increase N-Terminal Pro-B-Type Natriuretic Peptide level, microvascular dysfunction, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0
12

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 213 publications
(253 reference statements)
0
14
0
12
Order By: Relevance
“…Biopsy samples obtained from patients in the acute phase of TTS are similar to those resulting from the direct effects observed after catecholamine-induced cardiotoxicity (16). Evidence from clinical studies supports the hypothesis that excess catecholamine serves as triggers for TTS (15,16,(19)(20)(21). Paur et al (24) reported an animal study concerning TTS that revealed a high epinephrine concentration can induce LV apical ballooning by injecting an exogenously high-dose of epinephrine.…”
Section: Ev71-related Ahf and Ttsmentioning
confidence: 85%
See 2 more Smart Citations
“…Biopsy samples obtained from patients in the acute phase of TTS are similar to those resulting from the direct effects observed after catecholamine-induced cardiotoxicity (16). Evidence from clinical studies supports the hypothesis that excess catecholamine serves as triggers for TTS (15,16,(19)(20)(21). Paur et al (24) reported an animal study concerning TTS that revealed a high epinephrine concentration can induce LV apical ballooning by injecting an exogenously high-dose of epinephrine.…”
Section: Ev71-related Ahf and Ttsmentioning
confidence: 85%
“…Catecholamines seem to play an important role in the pathogenesis of TTS, reflecting the comprehensive response of the cardiovascular system to either a sudden increase in the concentration of endogenous catecholamines, which is usually related to acute severe stress, or exogenous catecholamines (15,16,(19)(20)(21). Cases can be classified as primary or secondary TTS (23).…”
Section: Ev71-related Ahf and Ttsmentioning
confidence: 99%
See 1 more Smart Citation
“…A shortcoming of the study is that no coronary angiography had been carried out. Diagnosing TTS according to the Mayo Clinic criteria requires exclusion of coronary heart disease [2] .…”
mentioning
confidence: 99%
“…TTS may be complicated by heart failure [2] , ventricular arrhythmias [2] , or sudden cardiac death [3] . Why was a patient with symptomatic SARS-CoV-2 infection and TTS discharged to home isolation?…”
mentioning
confidence: 99%